2022
DOI: 10.1186/s12909-021-03098-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the implementation of community-based learning in public health: a mixed methods approach

Abstract: Background The French government has set up a community-based learning programme on health promotion for undergraduate health students to involve them in key public health objectives. At the University of Lyon, students first underwent formal instruction, including e-learning, lectures, and interactive seminars, and then became health educators for school pupils. The main objective of the present study was to assess the process of implementing this programme during the 2018–2019 academic year. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
5
0
2
Order By: Relevance
“…This was previously viewed as the most satisfactory aspect by 85% of the students questioned at the end of the first sanitary service [ 1 ]. Other studies have shown the importance of interdisciplinary work not only in raising students’ awareness of prevention and public health issues [ 26 ], but also in favouring teamwork in the practice of the health professions [ 27 , 28 ]. However, the integration of different health professions in the same seminar programme is not easy to achieve, as shown by the publications of other French sanitary service experiences where interventions were carried out by only one or two professions [ 23 , 25 , 26 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was previously viewed as the most satisfactory aspect by 85% of the students questioned at the end of the first sanitary service [ 1 ]. Other studies have shown the importance of interdisciplinary work not only in raising students’ awareness of prevention and public health issues [ 26 ], but also in favouring teamwork in the practice of the health professions [ 27 , 28 ]. However, the integration of different health professions in the same seminar programme is not easy to achieve, as shown by the publications of other French sanitary service experiences where interventions were carried out by only one or two professions [ 23 , 25 , 26 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown the importance of interdisciplinary work not only in raising students’ awareness of prevention and public health issues [ 26 ], but also in favouring teamwork in the practice of the health professions [ 27 , 28 ]. However, the integration of different health professions in the same seminar programme is not easy to achieve, as shown by the publications of other French sanitary service experiences where interventions were carried out by only one or two professions [ 23 , 25 , 26 , 29 ]. The main challenge was to harmonise the academic agendas of the five professions so that students could be available at the same time for training and for interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary healthcare physicians are essential in community-based medical education [14]. Through their mentorship, expertise, and engagement with learners and educators alike, they can help ensure that future generations of healthcare providers are well-prepared to meet the needs of their communities [15].…”
Section: Introductionmentioning
confidence: 99%
“…A nivel internacional se aplican políticas de implementación en todas las comunidades de instrucción donde reciben entrenamiento en aprendizaje online (Leblanc et al, 2022) y la evaluación de estos adiestramientos tiene efectos poco alentadores porque el nivel de conocimiento en competencias digitales de los docentes es regular y no era lo que se esperaba, siendo superados por los estudiantes (Huamán-Romaní et al, 2022), en el manejo de las Tecnologías de Información y Comunicación (TIC) a consecuencia del principal método de enseñanza e-learning. Con la poca preparación económica en países subdesarrollados, el sector educación es el más satisfecho porque logra mejores rendimientos académicos en sus estudiantes (Bossman y Agyei, 2022).…”
Section: Introductionunclassified